Identification Noise monitoring for students in SMAN 1 Tapaktuan - Alfy Ariswan; Dirja Nur Ilham; Rudi Arif Candra; Arie Budiansyah; Fauzun Atabiq (ITScience (Information Technology and Science), 2021)
A high school is a place that is used as a place for the learning and teaching process, so a comfortable place is needed from disturbances in the study room. The Design System for Noise Monitoring Devices as an Effort to Minimize Noise Based on the Internet of Things (IoT) is designed to create comfort in the learning and teaching process at SMAN Tapaktuan so that teachers can concentrate without disturbing the noise generated by students. This tool is controlled by nodemcu and a sound sensor as a noise detector with an appropriate output by sending notifications to the Blynk Application. How the tool works when the sound sensor detects a noise level between 30 dB to 49 dB then dfplayer will issue a warning in the form of a warning